Performa Reproduksi Udang Pisang Domestikasi Non-Ablasi Fenneropenaeus indicus - Abidin Nur; D. A. Widyany; L. Ruliaty; Z. Arifin; M. Soleh (Fakultas Ilmu Kelautan dan Perikanan (FIKP), Universitas Hasanuddin, 2022)
The aims of the study were to evaluate the reproductive performance of pond reared broodstock of Fenneropenaeus indicus without prior ablation for shrimp maturity. These technique being reported impair physiological process and finally offspring quality Pre-maturation was with (BFT) and without biofloc technology (non-BFT) system assessed during the trials. First trial, amount of 10 months old broodstock were acclimatized during four days before mating, while the second trial a total of 190 pairs shrimp at 11 months olds were culture separately (females and males) during four weeks and reared into biofloc system prior maturation performed. Molasse was used as carbon sources to maintain C/N ratio of 15:1. All maturation processed conducted using rectangular cement tanks at 10L and 14D condition. Shrimp fed on fresh diets consists of squid, oyster and live Nereis sp ca. 25% body weight (1:1:1). Daily water exchange rate of 100% in the morning and afternoon, respectively. It was found that the latency period from the trials (6-7 days) within the ranged of common intervals for F. indicus. However, daily spawners, nauplii production and postlarvae survival shows any significant differences (p<0,05) were 8.0% vs 11.4%; 33.850 vs 51.246 N spawner- and 30.7% vs 23.26%, respectively. Results finding shown that domesticated F. indicus can successfully produced healthy post larvae without prior broodstocks ablation. Study on BFT during pre-maturation of these species firstly report and there is the need for further research in terms of pre-maturation period, nutritional status of the broodstock, and compensatory growth in ponds.